The maternal and perinatal outcomes in heart disease in pregnancy in a tertiary care hospital - Konar, Lisley; Patil, Divya J.; Kumar, Vasantha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The incidence of cardiac diseases in pregnancy ranges from 1 to 3%. Pregnancy in women with heart disease is associated with considerable mortality and morbidity. Thorough prenatal care and team approach involving obstetricians, cardiologists, anaesthesiologists and neonatologists can improve the maternal and fetal outcome in these women. Rheumatic heart disease is still the leading cause of maternal heart disease during pregnancy in developing countries. Methods: Between February 2022 and August 2022, a retrospective research at the RL Jalappa Hospital in Kolar was carried out. Out of 764 deliveries made at the facility throughout the study period, 30 singleton pregnancies complicated with heart disease admitted department of obstetrics and gynaecology at different periods of gestation. The maternal and perinatal outcome was thus noted. Results: Out of 764 deliveries, 30 women were found to have been complicated with heart disease. Overall incidence was 3.9%. Rheumatic heart disease was the most common heart disease seen among them. The most common congenital heart disease present was atrial septal defect (ASD). The most common cause for LSCS was fetal distress. 93.3% of the babies delivered were shifted to NICU, with the most common cause being, preterm and low birth weight. No maternal mortality seen, though 1 neonatal mortality present due to extreme low birth weight. Conclusions: A multidisciplinary team approach including obstetrician, cardiologist, pediatrician and anesthesiologist is needed in the cases of pregnancy with heart disease to determine the mode of delivery, timing of delivery, change in anticoagulant drugs in pregnancy, type of anesthesia, care of neonate, and follow-up of mother for better maternal and fetal outcomes.